E-Book Based Hammer Throwing Training Model at the Age of 13-15 Years DKI Jakarta Province - Marini Marini; Yasep Setiakarnawijaya; Moch. Asmawi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research aims to develop a training model for basic hammer throwing techniques at the age of 13-15 years and determine the effectiveness of the training model that has been developed. The problem that is the basis for conducting this research is that several literatures have not found a hammer throwing training model for 13-15 year olds in DKI Jakarta Province using an e-book basis. The method used in this research is Borg and Gall research and development through 10 development steps. Participants involved in the small group test were 15 athletes in DKI Jakarta Province and in the large group test 32 athletes. Then the participants involved in testing the effectiveness of the model were 32 athletes who were divided into 2, namely 16 athletes in the control group and 16 athletes in the experimental group. Based on the results of the N-Gain Score (%) test calculation, it shows that the average value of the N-Gain Score for the experimental group is 81.4321 or 81.43%, which is included in the effective category. Meanwhile, the average N-Gain Score for the control group was 34.88 or 34.88%, which was included in the Ineffective category. From the results of these calculations it can be seen that the use of the training model in the experimental group was effective in improving basic hammer throwing technique skills.